2022
DOI: 10.3390/fermentation8110578
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Synthesis Efficiency of Amino Acids Such as L-Lysine by Assembling Artificial Cellulosome Elements Dockerin Protein In Vivo

Abstract: Cellulosome is a highly efficient multi-enzyme self-assembly system and is found on the extracellular surface or in the free environment of microorganisms. However, with a lack of Ca2+ in vivo, cellulosome assembly is challenging. In this study, a novel design method was used to directionally modify the Ca2+-binding site, and four double-site dockerin A (DocA) mutants were obtained. At a Ca2+ concentration between 1.00 × 10−7 and 1.00 × 10−4 M, the mutant DocA-D3 had the strongest binding capacity to cohesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The inducible promoter Ptrc, aspC, cohA, panD and docA were cloned into pET28a (+) plasmid by selecting restriction enzyme sites EcoR I and Not I. DocA is an intracellular mutant that has undergone activity verification. Li et al (2022b) have confirmed that DocA can bind and assemble within cells, and improve product synthesis. The target fragment was cloned into a pET28a (+) plasmid.…”
Section: Construction and Transformation Of Recombinant Plasmidsmentioning
confidence: 66%
“…The inducible promoter Ptrc, aspC, cohA, panD and docA were cloned into pET28a (+) plasmid by selecting restriction enzyme sites EcoR I and Not I. DocA is an intracellular mutant that has undergone activity verification. Li et al (2022b) have confirmed that DocA can bind and assemble within cells, and improve product synthesis. The target fragment was cloned into a pET28a (+) plasmid.…”
Section: Construction and Transformation Of Recombinant Plasmidsmentioning
confidence: 66%
“…After induction, the fermentation time was less than 40 h, with sampling and testing every 4 h. The concentration of bacterial cells was determined using an ultraviolet spectrophotometer (UV-6100, METASH, Shanghai, China) to detect the absorbance of the sample at 600 nm after dilution. Glucose and L-lysine contents were measured using a biosensor (BSA-90, Jinan Yanke Co., Ltd., Jinan, China) [34].…”
Section: Assembly and Detection Of Key Enzymes In L-lysine Fermentationmentioning
confidence: 99%